Two new species of Neotropical Leptomorphus Curtis (Diptera: Mycetophilidae) - Fitzgerald, Scott J. (Zootaxa, 2021)
Two new species of Leptomorphus Curtis, L. guatemalensis sp. n. and L. juxtafurcatus sp. n., are described from Guatemala, figured, and compared with congeners. The new species belong to the clade including the “furcatus” and “walkeri” species-groups as defined by Borkent & Wheeler (2012). L. guatemalensis sp. n. can be recognized by the gonocoxite bulbous and crescent-shaped with the apex asetose and spatula-like, but remains without a clear sister-species. Based on the structure of the male terminalia, particularly the presence of submedian, pointed lobes on sternite nine, L. juxtafurcatus sp. n. is suggested to be the sister-species to L. furcatus Borkent from the southwestern USA and northern Mexico; these species can be distinguished by the form of the gonocoxites.